2020
DOI: 10.1177/0960327119898748
|View full text |Cite
|
Sign up to set email alerts
|

Presence of melamine in human milk and the evaluation of the effects on mother–infant pairs in a cohort study

Abstract: Melamine contamination is a recent public health problem emerging globally. Present study aimed to detect the rate of melamine presence in human milk in a cohort study and to evaluate any possible differences in maternal–infant pair characteristics such as breastfeeding status, crying and sleep problems of infants, maternal postpartum depression, maternal–infant bonding, infant and maternal anthropometry, and maternal complete blood count caused by the melamine exposure. Mothers of infants born in Şanlıurfa we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 25 publications
(38 reference statements)
1
1
0
Order By: Relevance
“…Our pregnant study population's range of melamine exposure is below those in some studies (Lam et al, 2009;Liu et al, 2017) but similar to those found in NHANES (Guo et al, 2020). Additionally, our population is exposed during the prenatal period which could increase the risk for developmental effects in the children due to unique or heightened periods of developmental susceptibility and the potential for maternal-fetal transfer via the placenta (Jingbin et al, 2010;Wu et al, 2020) and breastmilk (Chan et al, 2011;Yalcin et al, 2020). Developmental exposure to melamine and melamine analogs could additionally affect other health endpoints as supported by animal studies reporting fetal growth restriction, incomplete ossification, and spatial cognitive impairments in animal studies (An and Sun, 2017;Kim et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our pregnant study population's range of melamine exposure is below those in some studies (Lam et al, 2009;Liu et al, 2017) but similar to those found in NHANES (Guo et al, 2020). Additionally, our population is exposed during the prenatal period which could increase the risk for developmental effects in the children due to unique or heightened periods of developmental susceptibility and the potential for maternal-fetal transfer via the placenta (Jingbin et al, 2010;Wu et al, 2020) and breastmilk (Chan et al, 2011;Yalcin et al, 2020). Developmental exposure to melamine and melamine analogs could additionally affect other health endpoints as supported by animal studies reporting fetal growth restriction, incomplete ossification, and spatial cognitive impairments in animal studies (An and Sun, 2017;Kim et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, FDA issued a letter in 2008 to alert the food manufacturing industry, increased surveillance in food products, and developed analytic methods to better determine melamine and its derivatives (Kuehn, 2009;FDA 2021bb). However, such regulations are limited to food items and human exposure is still possible through contact with consumer products and the residues in the ambient environment (Shin et al, 2020;Takazawa et al, 2020;Zheng et al, 2020;Zhu et al, 2019;Zhu and Kannan, 2018a;b, 2019b, 2020ab). Other chemicals, such as aniline, o-/m-toluidine, p-anisidine, and 3-chloroaniline, were also associated with calendar year although the underlying reason is unclear.…”
Section: Discussionmentioning
confidence: 99%